Anomalies, Time Signals, And Stock Prices In The KLSE - Lai , Ming Ming (2002)
Financial pundits the world over pontificate that investors must strive for above average returns in their investments. Hence, the search for market anomalies and trading rules which may bring forth abnormal profit opportunities. This study integrates and incorporates the winner-loser anomaly and technical trading rules in investment decisions in the Malaysian stock market through comprehensive examination of these issues over the full-sample and four sub-sample periods, during both bullish and bearish periods.